Probing the stability of the food colourant R-phycoerythrin from dried Nori flakes. (16th April 2022) - Simovic, Ana; Combet, Sophie; Cirkovic Velickovic, Tanja; Nikolic, Milan; Minic, Simeon
Highlights: R-phycoerythrin (R-PE) is purified and characterized from dried Nori flakes. R-PE is being unfolded by temperature and pressure through a two-transition process. Opposite to thermal, the high-pressure (HP) treatment preserves the colour of R-PE. Tetrapyrrole chromophores of R-PE are capable of binding Cu 2+ and Zn 2+ ions. The binding of Cu 2+ and Zn 2+ ions does not impair the folded state of R-PE. Abstract: This study aimed to characterise the stability of R-phycoerythrin (R-PE), a vivid natural colourant with emerging potential for application in the food industry. High-quality (A560 /A280 ≥ 5), native (α-helix content 75%) R-PE was purified from commercial dried Nori ( Porphyra sp.) flakes. Thermal unfolding revealed two transitions (at 56 and 72 °C), ascribed to different protein subunits. Contrary to elevated temperature, high-pressure (HP) treatment showed significant advantages: The R-PE unfolding was partly reversible and the colour bleaching was minimal. Binding of Cu 2+ (6.3 × 10 5 M −1 ) and Zn 2+ (1.7 × 10 3 M −1 ) influenced conformational changes in the protein tetrapyrrole chromophore without affecting R-PE structure and stability (colour). The results give new insights into the stability of R-PE suggesting its usefulness for the replacement of toxic synthetic dyes. Preservation of the red colour of R-PE could be considered in fortified food and beverages by HP processing. R-PE may act as a biosensor for Cu 2+ in aquatic systems.